A scoping and critical review of properties, standards, and regulations of oxo-biodegradable plastics - Juan Carlos Salcedo Reyes; Octavio Alejandro Castañeda Uribe; Luis David Gómez Méndez; Aura Marina Pedroza Rodríguez; Raúl A. Poutou-Piñales (Universitas Scientiarum)
Based on recent scientific-technical developments referring to the transformation and biodegradation mechanisms of plastic compounds, progress has been made both in the conceptualization of relevant definitions and in the development of technical standards that allow determining, in a more precise and reproducible way, the ratio of biodegradability of a determined material. From these advances, they have developed, furthermore, the so-called oxo-biodegradable plastics, in which pro-oxidant additives are added to the raw polymer in such a way that allow a optimal abiotic transformation process (photo/thermo oxidation), producing the fragmentation of the material under suitable conditions for its simultaneous or successive biotic degradation (enzymatic oxidation). Although, currently, oxobiodegradable plastics are widely used in different applications such as, for example, in agriculture and single-use plastics, until very recently a technical standard was developed that allows determining the relative degradation ratio of different types of plastics under abiotic and biotic conditions. This process implies that for producers to be able to use specific terms of bio-degradation and oxo-biodegradation for advertising purposes that claim to offer an environmentally friendly product, the relevant entities must carry out metrological tests in light of the new definitions and technical standards. Furthermore, a large amount of specialized literature has been generated in which the bio-degradation ratio of oxobiodegradable plastics is determined in very specific environments and conditions. This review gives a detailed account of the different definitions and scientific concepts involved in oxo-/bio- degradation and shows how these concepts have evolved over time. It also shows the evolution of the technical standards, which, in general, are adapted to the new scientific and technical developments in the field of plastics. Finally, a detailed analysis of results reported in the scientific literature shows the dependence of oxo-biodegradation on different parameters (UV radiation, temperature, exposure time, type of enzymes), specific environments (soil, composting, waste, recycling, etc.), different types of plastics (LDPE, HDPE, LLDPE, pro-oxidant additives) and, finally, on different analytical techniques used (FTIR, DSC, TGA, SEM, tensile test).